“Obtención química de carbón activado a partir del endocarpo del coco (coccus nucifera) en la Región de San Martín” - Bardalez Viena, Alex (2005)
This research work reports the methodology used for the chemical obtaining of activated carbon from the coconut's endocarp, a palm fruit widely cultivated in many places around the world, whose endocarp is considered as waste material in our region. The coconut's endocarp was chosen as raw material because: it possesses a high combustion power, that indicates a high carbon content, which is an essential parameter for the obtaining of an activated carbon; and more important, to give added value to waste. The aim is to determine the appropriate technology and the parameters to be used in arder to produce activated carbon. The method of chemical activation employing Phosphoric Acid and Sulfuric Acid, as activating agents, was used for that purpose. The acids were used in concentrations of 35 ppm, 40 ppm, 45 ppm, and 50 ppm. The carbonization-activation was done at 600 ºC. The physical-chemical characteristics of both, row material and end product, were evaluated. Since there were no differences between varieties, and according to the used methodology, the optimal treatment consisted on utilizing phosphoric acid as activating agent in a concentration of 50 ppm. lt was obtained a carbonization industrialization output of 26.79%. Which was considerad as satisfactory and clase to the industrial values for the different row material s. The produced pulverulent active carbon meets all technical spedfications required by INDECOPY in arder to be commercialized in the market. lt could be used in the aleche! beverage industry and the beer industry, to eliminate color traces, organic material, as well as other odors and flavors.